2020
DOI: 10.1021/acsami.0c17333
|View full text |Cite
|
Sign up to set email alerts
|

KN95 and N95 Respirators Retain Filtration Efficiency despite a Loss of Dipole Charge during Decontamination

Abstract: N95 decontamination protocols and KN95 respirators have been described as solutions to a lack of personal protective equipment. However, there are a few material science studies that characterize the charge distribution and physical changes accompanying disinfection treatments, particularly heating. Here, we report the filtration efficiency, dipole charge density, and fiber integrity of N95 and KN95 respirators before and after various decontamination methods. We found that the filter layers in N95 and KN95 re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 59 publications
5
79
1
Order By: Relevance
“…This result showed that as the flow rate decreased, the fiber diameter greatly decreased and became more uniform, and could effectively improve the impedance value and the high-pressure difference. For the nanofiber mask, the thinner and denser the fiber diameters are, the more PFE and pressure difference can meet the requirements of CNS 14,774 specifications for general medical masks [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result showed that as the flow rate decreased, the fiber diameter greatly decreased and became more uniform, and could effectively improve the impedance value and the high-pressure difference. For the nanofiber mask, the thinner and denser the fiber diameters are, the more PFE and pressure difference can meet the requirements of CNS 14,774 specifications for general medical masks [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, the influence of PFE was further explained in Table S8 , Figure 5 , that as the spinning time increased, the accumulated nanofiber membranes increased. When the collection time reached 6 h, the PFE increased from 38.6% to 83.2%, and the pressure difference was fixed at 4.7 mmH 2 O/cm 2 , which meets the requirements of CNS 14,774 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 c) [ 78 ]. The spunbonded PP features a weak electric charge, with a dipole charge density less than 0.5 ÎŒC/m 2 [ 79 ]. Consequently, this layer has a rather poor PFE of only 6–10% [ 78 , 79 ].…”
Section: Standards Testing Methods and Efficacy Of Face Masksmentioning
confidence: 99%
“…person coughs, sneezes, or speaks [4]. Most of these particles fall at a distance less than one meter from the emitter.…”
mentioning
confidence: 99%
“…Various types of face masks have been designed, for instance, N95s with three structural layers and KN95s that consist of four layers. Both types retain particles up to 0.3 microns with 95% efficiency, so they are recommended for healthcare personnel [4].…”
mentioning
confidence: 99%